RESPON SISWA TERHADAP FILM DOKUMENTER SEBAGAI MEDIA PEMBELAJARAN MATERI PLANTAE KELAS X MAN SAMBAS - Ulfa, Mutia; Putri Panjaitan, Ruqiah Ganda; Wahyuni, Eko Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study is aimed at identifying the students of Plantae class X MAN Sambas. The research method used is descriptive method with survey research form. TheÂ  populatin in this research is the students of class XI MAN Sambas which consists of class XI MIA, XI IIS, and XI IIK. Subjects in this study were 34 students of class XI MIA MAN Sambas. The procedure in this research consists of three phase, the preparation phase, the implementation phase, and the final phase. The research instrument used is a questionnaire. The questionnaire fron in this study is a closed questionnaire. Response assessment consists of two criteria: responses and reactions. The response criterion consists of two aspects: format and relevance. While the reaction criteria consists of three aspects: attention, satisfaction and confidence. The questionnaire consists of 20 statements with 10 positiveÂ  statements and 10 negative statements. The questionnaire analysis shows that the students responded positively to the documentary on Plantae material with the average percentage of 83.84%.Keywords: Students' responses, Documentary film, Plantae Â